Basic research on determining optical properties of tissues in vivo by measuring diffuse reflectance with a charge-coupled device - Sun, Ping; Cao, Xianping; Yang, Runqiu; Xie, Fenghua; Ding, Jiaqi; Zhang, Fuqiang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
We measured the absorption coefficient and the reduced scattering coefficient of Intralipid solution and human forearm tissues in vivo by measuring diffuse reflectance with a charge-coupled device, examining the techniques involved. The experimental results indicate that the error is less than or equal to 8% using the diffusion theory, under the condition that the reduced scattering coefficient is one order of magnitude greater than the absorption coefficient. The stability and precision of optical property measurements are significantly improved by using the multistep iterative fitting method and using the ring-zone-constraint method to determine the diffuse reflectance center. The efficiency of reverse algorithm is greatly enhanced by selecting a one-dimensional array on the straight line crossing both the entry point and the diffusion center for fitting.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 541-555
Keywords: optyka; diffusion theory; turbid media